(untitled) (Journal of Pathology of Nepal, 2023)
Background: Human blood till date has no substitute. Transfusion of blood and its components is a lifesaving procedure. Hence, optimum utilization and minimum wastage of blood and its components should be strictly monitored. Materials and Methods: This is a prospective study conducted on data collected from the blood bank of B.P. Koirala Institute of Health Sciences, Dharan, Nepal for a duration of 1 year from year 2015 to 2016. The sample size was calculated by using systematic random sampling with every third sampling interval sample collection method. The study included usage and wastage of packed red blood cells, platelet concentrate, fresh frozen plasma, and cryoprecipitate including data on the supply of blood components to different departments, age distribution, gender distribution, and distribution of blood components based on blood groups. Results: A total of 1641 units of blood component were included in the study. A total of 92.9% (1524 units) were used and 7.13% (117 units) were wasted. The renal disorder was the most common cause of blood component utilization. The medicine department utilized the majority of the blood components. The expiry was the most common cause of wastage. Among the wasted blood components, platelet concentrate was the maximum. Conclusion: Blood components are a life-saving resource. It should be evaluated and analyzed properly for utilization in a justifiable manner. The hospital should act in accordance so that maximum blood components are utilized in a safe manner and waste is minimized to the least.